Broadsheets: single-sheet publishing in the first age of print - Pettegree, Andrew (Library of the written word, 2017)
"This volume offers an expansive survey of the role of single-sheet publishing in the European print industry during the first two centuries after the invention of printing. Drawing on new materials made available during the compilation of the Universal Short Title Catalogue, the twenty contributors explore the extraordinary range of broadsheet publishing and its contribution to government, pedagogy, religious devotion and entertainment culture. Long disregarded as ephemera or cheap print, broadsheets emerge both as a crucial communication medium and an essential underpinning of the economics of the publishing industry"--Provided by publisher